2020
DOI: 10.46497/archrheumatol.2021.8193
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Self-Reported Capacity to Walk, Jog and Run in Individuals With Systemic Lupus Erythematosus

Abstract: Objectives This study aims to explore how disease and health-related quality of life (HRQOL) factors are associated with self-reported physical capacity in walking, jogging and running in systemic lupus erythematosus (SLE). Patients and methods This cross-sectional study is part of an ongoing cohort research project which started in 2014. A total of 198 patients (21 males, 177 females; mean age 51.5±16.1 years; range, 20 to 82 years) with SLE answered a question concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Lupus is categorized as a prototypic autoimmune disease, as it can attack the healthy tissues of the body and affect the way the body fights infections (Pessato et al 2018). Lupus is also a chronic inflammatory disease associated with exacerbations and remissions within a broad spectrum ranging from very mild forms to major organ involvement that can cause significant morbidity and mortality (Kinikli 2021). Lupus can affect the body both physically and mentally, with symptoms ranging from mild to severe.…”
Section: What Is Lupus?mentioning
confidence: 99%
See 1 more Smart Citation
“…Lupus is categorized as a prototypic autoimmune disease, as it can attack the healthy tissues of the body and affect the way the body fights infections (Pessato et al 2018). Lupus is also a chronic inflammatory disease associated with exacerbations and remissions within a broad spectrum ranging from very mild forms to major organ involvement that can cause significant morbidity and mortality (Kinikli 2021). Lupus can affect the body both physically and mentally, with symptoms ranging from mild to severe.…”
Section: What Is Lupus?mentioning
confidence: 99%
“…In another study conducted by Kinikli et al (2021), researchers wanted to assess lupus disease activity utilizing specific questionnaires where the participants had to self-report their physical activity levels, capacity, anxiety, depression, and quality of life. The study found that patients who reported low physical ability were older, had longer disease duration, more organ damage, and revealed a lower overall quality of life, less mobility, less usual activities, more pain, and depressive symptoms.…”
Section: Previous Studiesmentioning
confidence: 99%